Hydrogels containing botanical repellents encapsulated in zein nanoparticles for crop protection - Oliveira, Jhones Luiz de [UNESP] (2020)
Essential oils and their derivatives are eco-friendly biopesticides that can contribute to reducing the use of synthetic pesticides in agricultural pest control, offering advantages including less harm to humans and the environment. This work concerns hydrogel-based repellent systems containing botanical compounds that were emulsified or encapsulated in zein nanoparticles. The hydrogels were prepared according to a two-step process involving molding and crosslinking. They presented good rheological properties, even at elevated temperature (40 oC), a swelling degree of about 30±1.2%, and were able to modulate the release of active compounds. The hydrogels containing botanical compounds presented high repellency (>80%) against two important agricultural pests: whitefly (Bemisia tabaci) and two-spotted spider mite (Tetranychus urticae). These repellent systems are promising for use in sustainable agriculture, since they are based on the use of natural substances for both the matrices and the active agents. It is noteworthy that the systems can be used without direct contact with plants, which minimizes any problems related to phytotoxicity.